2020
DOI: 10.1186/s12903-020-01192-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of primary oral and oropharyngeal squamous cell carcinoma in inhabitants of Beijing, China—a 10-year continuous single-center study

Abstract: Background: This study aimed to describe some of the characteristics of the inhabitants of Beijing with oral and oropharyngeal squamous cell carcinoma (OSCC) who had received treatment at the Stomatology Hospital of Peking University and to analyze the survival rate and the prognostic factors of patients following surgical treatment. Methods: Data for 603 consecutive cases with primary OSCC between 2004 and 2013 were obtained from the Stomatology Hospital of Peking University. Clinical data including age, sex,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 24 publications
8
9
0
Order By: Relevance
“…( 1 ) (HR: 1.82; 95% CI, 1.18-2.78) for OSCC. Individuals diagnosed with lip SCC (HR: 1.97; 95% CI, 1.32-2.95), OSCC (HR: 2.19; 95% CI, 1.88-2.55), and OPSCC (HR: 2.51; 95% CI, 2.09-3.00) with advanced-stage (stages III-IV) tumours were more likely to die than patients with early-stage disease, which was an important independent determinant of OS, corroborating the findings reported in earlier studies ( 7 , 8 , 15 , 22 , 27 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…( 1 ) (HR: 1.82; 95% CI, 1.18-2.78) for OSCC. Individuals diagnosed with lip SCC (HR: 1.97; 95% CI, 1.32-2.95), OSCC (HR: 2.19; 95% CI, 1.88-2.55), and OPSCC (HR: 2.51; 95% CI, 2.09-3.00) with advanced-stage (stages III-IV) tumours were more likely to die than patients with early-stage disease, which was an important independent determinant of OS, corroborating the findings reported in earlier studies ( 7 , 8 , 15 , 22 , 27 ).…”
Section: Discussionsupporting
confidence: 89%
“…When lip SCC was exclusively analysed, previous studies reported that the lower lip was the most commonly affected site ( 10 , 15 , 23 ), similar to our findings. In the oral cavity, according to previous reports ( 7 , 9 , 14 , 22 ) and our results, the tongue (excluding the base of the tongue) was the most commonly affected subsite. However, in India and surrounding countries, the most frequent subsite of OSCC was the buccal mucosa, as a repercussion of the habit of chewing tobacco ( 24 ).…”
Section: Discussionsupporting
confidence: 85%
“…Long-term survival analysis allows the assessment of several clinicopathologic parameters over the period of time, and to evaluate their changing influence on patient mortality. A single-centre study of China has reported a decrease in survival rate from 71% at 3-year, to 64% at 5-year and 54% at 10-years for OSCC [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, the prognosis of OSCC is highly heterogeneous, with an overall 5-year survival rate of approximately 64%, and the median survival duration for patients with locoregionally recurrent or metastatic OSCC is 8~10 months (31,32). Oral malignancies progress through four stages; in the early stage (stages I and II), the 5-year survival rate is approximately 80%.…”
Section: Discussionmentioning
confidence: 99%